Finite element modelling of the explosive blast response of carbon fibre-polymer laminates. (15th November 2019) - Gargano, A.; Das, R.; Mouritz, A.P.
Abstract: A finite element (FE) modelling methodology is presented to analyse the dynamic response of carbon fibre reinforced polymer laminates when loaded by the shock wave generated by an airborne explosive blast. An FE model is developed to calculate the out-of-plane deformation of laminates over the entire duration of an explosive blast loading event. The FE model can also predict the initiation and propagation of delamination cracking and ply rupture in laminates. The response of the composite target plates to explosive blast loading was modelled in the FE program Abaqus using an explicit solver. The explosive air blast load was modelled using the ConWep algorithm. The accuracy of the FE model is assessed using experimental data obtained from small-scale far-field and near-field explosive blast tests performed on carbon-polyester and carbon-vinyl ester laminates. The FE model can predict the dynamic deformation of the laminates to within an accuracy of ~10%. The model can also accurately determine delamination cracks and broken plies.